Addition of IMP3 to L1CAM for discrimination between low- and high-grade endometrial carcinomas: a European Network for Individualised Treatment of Endometrial Cancer collaboration study - Visser, Nicole C M; van der Putten, Louis J M; van Egerschot, Alex; Van de Vijver, Koen K; Santacana, Maria; Bronsert, Peter; Hirschfeld, Marc; Colas, Eva; Gil-Moreno, Antonio; Garcia, Angel; Mancebo, Gemma; Alameda, Francesc; et al. (Human pathology, 2019)
Discrimination between low- and high-grade endometrial carcinomas (ECs) is clinically relevant but can be challenging for pathologists, with moderate interobserver agreement. Insulin-like growth factor-II mRNA-binding protein 3 (IMP3) is an oncofoetal protein that is associated with nonendometrioid endometrial carcinomas but has been limited studied in endometrioid carcinomas. The aim of this study is to investigate the diagnostic and prognostic value of IMP3 in the discrimination between low- and high-grade ECs and its added value to L1CAM. IMP3 and L1CAM expression was assessed in tumors from 378 patients treated for EC at 1 of 9 participating European Network for Individualised Treatment of Endometrial Cancer centers. IMP3 was expressed in 24.6% of the tumors. In general, IMP3 was more homogeneously expressed than L1CAM. IMP3 expression was significantly associated with advanced stage, nonendometrioid histology, grade 3 tumors, deep myometrial invasion, lymphovascular space invasion, distant recurrences, overall mortality, and disease-related mortality. Simultaneous absence of IMP3 and L1CAM expression showed the highest accuracy for identifying low-grade carcinomas (area under the curve 0.766), whereas simultaneous expression of IMP3 and L1CAM was strongly associated with high-grade carcinomas (odds ratio 19.7; 95% confidence interval 9.2-42.2). Even within endometrioid carcinomas, this combination remained superior to IMP3 and L1CAM alone (odds ratio 8.6; 95% confidence interval 3.4-21.9). In conclusion, IMP3 has good diagnostic value and together with L1CAM represents the optimal combination of diagnostic markers for discrimination between low- and high-grade ECs compared to IMP3 and L1CAM alone. Because of the homogenous expression of IMP3, this marker might be valuable in preoperative biopsies when compared to the more patchy L1CAM expression.
Keywords: nádory endometria; dospělí; Female; Adult; ženské pohlaví; proteiny vázající RNA; lidé; Sensitivity and Specificity; Neoplasm Grading; Prognostic biomarker; Diagnostic biomarker; Aged, 80 and over; senzitivita a specificita; IMP3; Neural Cell Adhesion Molecule L1; stupeň nádoru; nádorové biomarkery; Aged; molekula buněčné adheze nervové L1; L1CAM; RNA-Binding Proteins; Biomarkers, Tumor; lidé středního věku; Endometrial Neoplasms; senioři nad 80 let; senioři; Endometrial carcinoma; Middle Aged; Humans